Risikoscores für chronisch nierenkranke Menschen - Schneider, Markus; Eckardt, Kai-Uwe (Deutsche Medizinische Wochenschrift, 2019)
Assessing the risk of adverse outcomes associated with chronic kidney disease (CKD) is important for physicians and affected patients alike. Categorizing CKD according to the cause-GFR category-albuminuria category (CGA)-classification system proposed by KDIGO already provides a semi-quantitative assessment of risks. The more recent development of the Tangri-formula provides a means to quantify the risk of progression for patients with CKD stage G3a-G5 (eGFR 10-59ml/min/1.73m 2) to kidney failure requiring kidney replacement therapy. To use this formula, the variables age, sex, eGFR and albuminuria are required (4-variable equation). An extended formula with the additional parameters calcium, phosphate, bicarbonate and albumin (8-variable equation) allows an even more precise estimation of progression risk. In patients with advanced CKD, stage G4 or higher (GFR category ≥4, i.e. eGFR <30ml/min/1.73m 2), models recently developed by the CKD-prognosis consortium can not only be used to predict the risk of kidney failure but also the risk of cardiovascular disease events and death. The risk estimators can be accessed through websites (http://kidneyfailurerisk.com, http://www.ckdpcrisk.org/lowgfrevents/) and via downloading of the respective apps. These novel tools may prove useful for health care decisions and as a basis for discussions with CKD patients.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cardiovascular diseases; kidney; kidney disease; prognosis; risk